2018
DOI: 10.1186/s12913-018-2888-1
|View full text |Cite
|
Sign up to set email alerts
|

The gravitational force of mental health services: distance decay effects in a rural Swiss service area

Abstract: BackgroundPrevious research suggested a distance decay effect in health services systems, with people living closer to service facilities being more likely to use them.MethodIn this ecological cross sectional study, we conducted spatial and statistical analyses in a Swiss mental health services system being legally bound to provide primary mental health care to approximately 620,000 inhabitants. We examined a cohort of all patients who were over 18 years old and who were treated in the mental health services s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
6
24
0
4
Order By: Relevance
“…"Distance to the hospital" has been known for more than 50 years to in uence the hospital admission rate in mental disorders (43,44) or service utilization in outpatient facilities (45). We could con rm in our dataset that lower travelling distances between residence and hospital are associated with a higher readmission risk.…”
Section: Discussionmentioning
confidence: 78%
“…"Distance to the hospital" has been known for more than 50 years to in uence the hospital admission rate in mental disorders (43,44) or service utilization in outpatient facilities (45). We could con rm in our dataset that lower travelling distances between residence and hospital are associated with a higher readmission risk.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have shown that increase in distance decreases the likelihood of service utilization in mental health. [8][9][10][12][13][14] Similarly, there was significant association of proximity to hospital with LoS, those from same and nearby districts had shorter LoS as compared to others. In our clinical experience, those from nearby places, who could follow up regularly to OPD are discharged earlier as compared to those from faraway places who could have difficulty in following up regularly.…”
Section: Discussionmentioning
confidence: 93%
“…This was done as literature have shown the role of proximity to the service in mental health service utilization. [8][9][10] The data were entered into MS Excel and analysed using the SPSS version 20.0. For descriptive statistics, percentage, mean, range and standard deviation were calculated.We used bivariate and multiple logistic regression analysis to find the strength of association of LoS with variables of interest and adjusted Odds Ratio (aOR) were calculated with 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
“…2004; Stulz et al . 2018; Wang & Luo 2005). Our findings corroborate these results and reflect the inequitable distribution of mental health nurses to provide quality and timely mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Access to community-based mental health services is influenced by: spatial factors such as physical availability and geographical distance, non-spatial determinants which include economic, cultural and social forces, and factors associated with the organization and arrangement of mental health systems (Wang & Luo 2005). Studies have consistently shown that the utilization of mental health services is reduced with increasing spatial distance and travel time (Almog et al 2004;Stulz et al 2018;Zulian et al 2011). These studies signal that people with mental health conditions in rural and remote areas are less likely to access mental health services due to distance and spatial availability.…”
Section: Introductionmentioning
confidence: 99%